Intraocular foreign body in the anterior chamber angle misdiagnosed as herpetic stromal keratitis - (:unkn) unknown (My University, 2023)
We report a case of a metallic intraocular foreign body (IOFB) retained in the anterior chamber (AC) angle that was masquerading as herpetic stromal keratitis. A 41-year-old male construction worker was referred to our ophthalmology clinic with the complaint of consistent blurred vision for 3 days in his left eye. He had no history of ocular trauma. The best-corrected visual acuity was found to be 10/10 in the right eye and 8/10 in the left eye. On slit-lamp examination of the anterior segment, the right eye was normal, while the left eye showed unilateral corneal edema and scarring, anterior lens capsule opacification, +2 cells in the AC, and the Seidel test was negative. Fundus examination was normal bilaterally. Despite there not being history of it, we still suspected ocular trauma considering the patient\"s occupational risk. Consequently, an orbital computed tomography imaging was performed which revealed a metallic-IOFB in the inferior iridocorneal angle. On the second follow-up day, the corneal edema regressed, and a gonioscopic examination of the affected eye was performed, showing a small foreign body embedded in the inferior iridocorneal angle of the AC. Subsequently, the IOFB was surgically removed using Barkan lens, and excellent visual results were achieved. This case emphasizes the importance of considering IOFB in the differential diagnosis of patients with unilateral corneal edema and anterior lens capsule opacification. Fur-thermore, the presence of IOFB should be definitely excluded in patients with occupational risk of ocular trauma even if there is no history of trauma. More awareness about the proper use of eye protection should be raised to circumvent penetrating ocular-trauma.
Herpetik stromal keratit olarak yanlış tanı konmuş ön kamara açısında göz içi yabancı cisim olgusu
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Anesteziyoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; ANESTEZİYOLOJİ; ACİL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; ANESTHESIOLOGY; EMERGENCY MEDICINE; Cerrahi; Anesteziyoloji ve Ağrı Tıbbı; Surgery; Anesthesiology and Pain Medicine